“I Can Relate”: Practice and Ethical Considerations for Eating Disorder Therapists with a History of an Eating Disorder - Beaton, Renee (Canadian Journal of Counselling and Psychotherapy, 2020)
There is a substantial subgroup of practising psychotherapeutic professionals in the treatment of eating disorders who have a history of an eating disorder themselves. These professionals encounter unique situations in their practice inherent to their experiential knowledge. Unfortunately, the stigma surrounding experiential knowledge and eating disorders, along with discrepancies about eating disorder recovery and the course of the disorder, creates challenges for therapists with a history of an eating disorder. The psychotherapeutic profession raises complex practice and ethical issues when therapists with a history of an eating disorder treat clients with an eating disorder. Therapists with a history of an eating disorder should consider a critical evaluation of the professional and ethical aspects they encounter within their work to ensure sound practice for both clients and themselves.